Behaviour of post released translocated greater one-horned rhinoceros (Rhinoceros unicornis) at Manas National Park, Assam, India - Dutta, Deba; Sharma, Amit; Mahanta, Rita; Swargowari, Anindya (Pachyderm, 2017)
A post-release study of the behaviour of 10 greater one-horned rhinoceros’ (Rhinoceros unicornis) translocated to Manas National Park, Assam, India was carried out to understand how each individual rhino behaves in a new environement. Distinct seasonal variation in activity was observed among the released rhinos. Maximum grazing activity was observed in the monsoon (June–September) and retreating monsoon (October–November) seasons while it was observed that the grazing rate decreased during the dry winter season (December–February). In the winter season, browsing activity was observed to increase. Resting activity was maximum during the winter and pre-monsoon (March–May) seasons. Walking activity of adult females and calves increased in the monsoon season, and was higher than that of adult males. It was observed that adult males wallowed more frequently during the monsoon season than adult females and calves. It was further observed that rhinos not only wallow for thermoregulatory purposes, but also readily eat aquatic plants. There was no drastic difference between behaviour patterns of translocated rhinos at Manas National Park and those of resident rhinos in Assam and Nepal. The rhinos’ overall behaviour in the different seasons indicated that the translocated rhino population has adapted well at Manas National Park. Une étude du comportement de 10 grands rhinocéros unicornes (Rhinoceros unicornis) transloqués au parc national de Manas dans l’Assam, en Inde, après leur libération a été réalisée pour comprendre comment chaque rhinocéros individuel se comporte dans un nouvel environnement. On a observé une variation saisonnière distincte de l’activité chez les rhinocéros libérés. On a observé une activité de pâturage maximale dans les saisons de la mousson (juin-septembre) et dans celle de la décroissance de la mousson (octobre-novembre) alors que l’on a observé que le taux de pâturage a diminué pendant la saison sèche d’hiver (décembre-février). En hiver, on a observé une augmentation de l’activité de brout. L’activité de repos a été maximale pendant les saisons d’hiver et de pré-mousson (mars-mai). L’activité de marche des femelles adultes et des bébés rhinocéros a augmenté pendant la saison de la mousson étant plus élevée que celle des mâles adultes. On a observé que les mâles adultes se vautraient plus fréquemment pendant la saison de la mousson que les femelles adultes ou les bébés rhinocéros. On a également observé que les rhinocéros se vautrent non seulement à des fins thermorégulatrices, mais aussi qu’ils consomment facilement des plantes aquatiques. Il n’y avait pas de différence drastique entre les comportements des rhinocéros transloqués au parc national de Manas et ceux des rhinocéros résidents dans l’Assam et au Népal. Le comportement général des rhinocéros dans les différentes saisons indique que la population des rhinocéros transloqués s’est bien adaptée au parc national Manas.